Students’ Readiness and Problems in Learning English through Blended Learning Environment - Sriwichai, Chuanpit (Asian Journal of Education and Training, 2020)
In academic year 2018, the University of Phayao commenced the application of blended learning approach which combines face-to-face class and online learning mode to teaching and learning English as a general education course for the first and second-year students. This study aims to explore students’ readiness for learning English course through blended learning environment and investigate problems and challenges that the students faced in their learning. Drawing upon 364 questionnaires with closed and open-ended questions along with focus group interviews with 20 interviewees, the findings revealed that students’ readiness for learning English through blended learning was at slightly high level. They tended to be able to learn English through the combination of two different learning modes. They believed that learning English in face-to-face classroom and online learning mode motivated them to be more self-disciplined and responsible for their own learning, and encouraged them to set up their own English learning plans and learning goals. However, the major problems and challenges the students confronted in learning included losing focus on learning in classroom due to considerable class size, limited access of online lessons caused by Learning Management System (LMS) severe crash, difficulty of online interaction with teachers and classmates, lack of experience and skills for digital tools, and time management for two learning modes.